SEJARAH PEMIKIRAN EKONOMI ISLAM KLASIK - Ruslan Husen Marasabessy (Jurnal Asy-Syukriyyah, 2016)
The development of Islamic economic theory starts from the revelation of the verses about the economy in the Qur'an, such as: Q.S. Al-Baqarah verse 275 and 279 on the sale and usury; Q.S. Al-Baqarah verse 282 of bookkeeping transactions; Q.S. Al-Maidah paragraph 1 of the contract; Q.S. An-Nisa 'verse 5 and 10 as well as Q.S. Al-Araf verse 31 about the search settings, care and spend their wealth. According to At-Tariqi, these verses show that Islam has set economic staple since pensyariatan Islam (time of the Prophet.), And methodically continued by his successors (rashidun). At this time, the shape perokonomian problems have not been very varied, so the theories that emerged was not diverse. It's just a very substantial from the development of this thinking is the commitment to the realization of the vision of Islam rahmatan lil 'alamin.